Hukum Perkawinan Dalam Pemberian Mahar: Nein Welin Di Duablolong - Elisabeth Trivonia Lali; Sepriliani Suryati Eltin Satung; Stefanus Don Rade (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
Marriage is a very important event in the life of our society. Marriage not only involves the bride and groom, but also the parents of both parties, their siblings, and even their respective families. In traditional traditions, marriage is not only important for living people, but is also a very meaningful event and receives full attention, and is attended by the spirits of the ancestors of both parties. A customary law community is a social community (paguyuban) consisting of people who are united because they have blood relations and/or a certain territory, have their own wealth, and are led by one or more people who are considered to have authority or power. Strength or they have values ​​as a guide to life and have no desire to separate each other.